2016
DOI: 10.1536/ihj.16-414
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Coronary Artery Disease

Abstract: SummaryGut microbiota have been attracting increased attention in many fields of medicine recently. We can perform a comprehensive analysis of gut microbiota using next-generation sequencing techniques together with bioinformatics technology, which expands our knowledge of a large ecosystem consisting of a host and gut microbiota. We summarize some reports about the correlations between gut microbiota and metabolic disorders, particularly atherosclerosis, and discuss future directions for the diagnostic or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 59 publications
0
47
0
1
Order By: Relevance
“…Bacillus. 66 A research showed that the structural changes in the GM could be used as a diagnostic marker for coronary heart disease. 67 Using a high-choline diet to feed ApoE-/-C57BL mice, results display that higher the serum TMAO level in mice, larger was the area of the sizeable atherosclerotic plaque .…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…Bacillus. 66 A research showed that the structural changes in the GM could be used as a diagnostic marker for coronary heart disease. 67 Using a high-choline diet to feed ApoE-/-C57BL mice, results display that higher the serum TMAO level in mice, larger was the area of the sizeable atherosclerotic plaque .…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…A total of 524 OUTs were obtained from 50 samples of all the groups. The valid data were clustered by taxon, OTUs abundance and Alpha/Beta diversity analysis [9]. The most abundant sequence was selected from each OTU as the representative sequence.…”
Section: Bioinformatics and Sequencing Data Analysismentioning
confidence: 99%
“…In recent years, with the development of genomics and molecular biology technologies, the relationship between intestinal microorganisms and the occurrence and development of diseases has attracted great attention [9][10][11][12]. The gastrointestinal tract is the largest microbial colonized organ in the body, as it maintains intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This may partially explain the beneficial effects of the so called Mediterranean diet, which is little atherogenic. Despite evidences, it is not clear whether the modification of the gut microbiota precedes metabolic changes or simply coincides with them, and causality cannot be ascertained (8).…”
Section: The Obesity Epidemicsmentioning
confidence: 99%